2019
DOI: 10.1002/ijc.32288
|View full text |Cite
|
Sign up to set email alerts
|

Multisite analysis of high‐grade serous epithelial ovarian cancers identifies genomic regions of focal and recurrent copy number alteration in 3q26.2 and 8q24.3

Abstract: High‐grade serous epithelial ovarian cancer (HGS‐EOC) is a systemic disease, with marked intra and interpatient tumor heterogeneity. The issue of spatial and temporal heterogeneity has long been overlooked, hampering the possibility to identify those genomic alterations that persist, before and after therapy, in the genome of all tumor cells across the different anatomical districts. This knowledge is the first step to clarify those molecular determinants that characterize the tumor biology of HGS‐EOC and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…The 3q26 amplicon is one of the most pervasively amplified chromosomal regions in cancer, and is known for promoting stem-like cancer cell characteristics [48]. This particular amplicon is estimated to occur in greater than 20% of all human cancers [48], with amplification rates as high as 75% in invasive lung SCC [75], and between 25 and 30% in ovarian cancer [51,76,77]. In addition to lung SCC and ovarian cancer, 3q26 amplification has been documented in esophageal SCC, head and neck SCC, and cervical cancer [49,50,[78][79][80].…”
Section: Discussionmentioning
confidence: 99%
“…The 3q26 amplicon is one of the most pervasively amplified chromosomal regions in cancer, and is known for promoting stem-like cancer cell characteristics [48]. This particular amplicon is estimated to occur in greater than 20% of all human cancers [48], with amplification rates as high as 75% in invasive lung SCC [75], and between 25 and 30% in ovarian cancer [51,76,77]. In addition to lung SCC and ovarian cancer, 3q26 amplification has been documented in esophageal SCC, head and neck SCC, and cervical cancer [49,50,[78][79][80].…”
Section: Discussionmentioning
confidence: 99%
“…However, supportively, a recent study in the highly heterogenous ovarian serous grade carcinomas consistently found amplifications (starting from 8q22.3 region) in ovarian tumor biopsies from different regions of the ovary, and also in the relapsed tumor tissue [50]. Future studies addressing inter-and intra-tumor heterogeneity in other cancer types will further highlight the potential clinical significance of amplifications in the 8q-region.…”
Section: Discussionmentioning
confidence: 52%
“…However, this study did not extend the analysis to other genes on chromosome 8. A recent study on therapeutic resistance in the highly heterogenous ovarian serous grade carcinomas consistently found amplifications in the 8q-region (starting from 8q22.3) in biopsies from different regions of the tumor, and the relapsed tumor tissue (Ballabio et al, 2019). These data suggest potential clinical significance of amplifications in the 8q-region.…”
Section: Discussionmentioning
confidence: 79%